Simulation of internal nitrogen release from bottom sediments in an urban lake using a nitrogen flux model - Gong, Ran; Wang, Hui-ya; Hu, Zhi-xin; Li, Yi-ping (Water Science and Engineering, 2023)
Nutrient release from sediment is considered a significant source for overlying water. Given that nutrient release mechanisms in sediment are complex and difficult to simulate, traditional approaches commonly use assigned parameter values to simulate these processes. In this study, a nitrogen flux model was developed and coupled with the water quality model of an urban lake. After parameter sensitivity analyses and model calibration and validation, this model was used to simulate nitrogen exchange at the sediment–water interface in eight scenarios. The results showed that sediment acted as a buffer in the sediment–water system. It could store or release nitrogen at any time, regulate the distribution of nitrogen between sediment and the water column, and provide algae with nitrogen. The most effective way to reduce nitrogen levels in urban lakes within a short time is to reduce external nitrogen loadings. However, sediment release might continue to contribute to the water column until a new balance is achieved. Therefore, effective measures for reducing sediment nitrogen should be developed as supplementary measures. Furthermore, model parameter sensitivity should be individually examined for different research subjects.